Racism in Foucauldian Security Studies: Biopolitics, Liberal War, and the Whitewashing of Colonial and Racial Violence. Issue 1 (28th December 2018) - Howell, Alison; Richter-Montpetit, Melanie
Abstract: This article argues that while Foucauldian security studies (FSS) scholarship on the biopolitics of security and liberal war has not ignored racism, these works largely replicate Foucault's whitewashing of the raciality and coloniality of modern power and violence. Drawing on Black, indigenous, postcolonial and decolonial studies, we show how Foucault's genealogy of biopower rests on an unspecified concept of the "human, " failing to account for how notions of "human" were constituted through the savage and slave other, how enslaved people were rendered into things, and how punitive, sovereign violence persists as a (settler) colonial technique of gratuitous, not merely instrumental, violence. FSS exacerbates these problems. This article challenges two core FSS propositions on liberal war: 1. that "human life cannot ever be secured, " which replicates Foucault's Eurocentric reliance on an unspecified "human" as the object of biopolitics; 2. that "everyone is (potentially) dangerous" and thus open to the punitive/lethal dimensions of liberal power, which reduces racism to a sorting process after the establishment of biopolitics and liberal war, rather than a precondition of it. This "methodological Whiteness" (Bhambra 2017a ) results in major oversights in FSS empirical genealogies of: state violence, twenty-first-century digital and molecular revolutions, labor, capital, and enslavement.